2007
DOI: 10.1007/s00114-007-0306-3
|View full text |Cite
|
Sign up to set email alerts
|

Where are the Sunday babies? III. Caesarean sections, decreased weekend births, and midwife involvement in Germany

Abstract: A previous study has shown a marked and continuing decline in weekend births in Germany between 1988 and 2003 (Lerchl, Naturwissenschaften 92:592-594, 2005). The present study was performed to investigate the possible influence of caesarean sections (CS) on weekend birth number and on the involvement of midwives in births for all 16 German states for the year 2003. In total, data from 706,721 births were sorted according to weekday of births and state, respectively, and the weekend births avoidance rates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…This finding is consistent with previous research that has found that, for low risk women, rates of episiotomy are elevated during business hours (Allen and Hanson, 2005). The past three decades have seen a steady decrease in weekend birth rates, thought to be attributable to managing the increasing rates of elective caesarean and induction of labour in the context of staff availability, scheduling practicalities and financial implications (Lerchl, 2005;Lerchl, 2008;Lerchl and Reinhard, 2008). While we acknowledge that affecting women's timing of birth is not possible without simultaneously denying women a normal birth, it is desirable to understand the mechanisms contributing to the observed association across different maternity care systems with different organisational structures (that affect staff availability and scheduling practices) in Australia.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with previous research that has found that, for low risk women, rates of episiotomy are elevated during business hours (Allen and Hanson, 2005). The past three decades have seen a steady decrease in weekend birth rates, thought to be attributable to managing the increasing rates of elective caesarean and induction of labour in the context of staff availability, scheduling practicalities and financial implications (Lerchl, 2005;Lerchl, 2008;Lerchl and Reinhard, 2008). While we acknowledge that affecting women's timing of birth is not possible without simultaneously denying women a normal birth, it is desirable to understand the mechanisms contributing to the observed association across different maternity care systems with different organisational structures (that affect staff availability and scheduling practices) in Australia.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to a previous study of normal birth [ 16 ], we did not identify timing of birth to be associated with the probability of experiencing normal birth. Rates of episiotomy [ 26 ] and instrumental vaginal birth [ 55 ] are shown to be higher during regular working hours, while the declining rate of weekend births appears to be related to the increasing rate of caesarean section [ 27 ]. Our lack of an association is potentially due to the stage at which timing of birth was introduced in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These differences are not attributable to case mix [ 22 , 23 ]. Rates of intervention have also been shown to increase for women outside midwifery-led continuity models of care [ 24 ], who receive care from a larger number of nurses in labour [ 25 ], give birth during business hours [ 26 , 27 ], or have continuous electronic fetal monitoring during labour [ 28 ]. More specifically, some practices have been associated with reduced need for regional anaesthesia during labour, such as water immersion during first stage labour [ 29 ], upright positioning and freedom of movement [ 30 ] and continuous one-to-one support [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…non-emergency) caesarean sections and elective labor inductions can be scheduled, a non-random distribution of the weekday numbers of births can be expected. In fact, several studies found marked differences between the numbers of births during the week and Saturdays and Sundays, respectively, for populations in the USA, UK, Australia and Germany (Goodman et al 2005;Gould et al 2003;Hendry 1981;MacFarlane 1978;Mathers 1983;Lerchl 2005Lerchl , 2007. The most recent studies by Goodman et al and Lerchl have demonstrated that in the USA and in Germany, there is a progressive trend towards fewer weekend births with no signs of abating.…”
Section: Introductionmentioning
confidence: 94%